Predictors and outcomes of different types of violent and cyclical relationships: a latent profile analysis - Keilholtz, Brooke (Kansas State University, 2023)
Despite awareness that intimate partner violence (IPV) and relationship cycling (RC) often co-occur, limited research has examined the ways in which these dynamics interact. Using the Dyadic Power-Social Influence Model (DPSIM) as a framework, this study aimed to identify typologies of violent and cyclical relationships, along with predictors and outcomes that were associated with these different types of relationships. A latent profile analysis with predictors and distal outcomes was performed using two rounds of data collected from Prolific, an online survey platform. From our analysis, five distinct profiles were identified with varying levels of RC and physical, psychological, sexual, and cyber IPV, including a high psychological IPV/ medium RC profile, a high IPV victimization/ high RC profile, a low IPV/ medium RC profile, a high sexual IPV/ low RC profile, and a high mutual IPV/ low RC profile. Once these distinct profile were identified, predictors (ties to relationship, interpersonal dependency, self-esteem, and powerlessness) of profile membership probability and associated outcomes (anxiety and depression, relationship satisfaction, and identity loss) of profiles membership were examined. These analyses identified profile-specific predictors and differing outcomes across the five types of violent and cyclical relationships, further distinguishing these profiles from one another. Awareness of these different relationship types and their relevant predictors and outcomes may aid in violence prevention and treatment efforts. Clinical and research implications are discussed below.
Keywords: Relationship typology; Intimate partner violence; Relationship cycling